O Plano de Desenvolvimento da Escola em foco: uma análise da educação no Ceará em tempos de ajustes neo-liberais - Diógenes, Elione Maria Nogueira (2005)
This study has an interpretative character and it was built with base in the scientific rigidity based in Pierre Bourdieu's conception (193012002). lt is a work located in a borderline with interpenetration in different areas: Social politics I Sociology I Education IScience politics. Your investigative and analytic composition contributes to a better understanding of the recent educational reforms happened in Ceará, indicating your political origin and your ideological function, besides emphasizing the analysis of the speech and of content, as fertile veins in studies of that nature. For so much, I defined as phenomenon of the study the "Plano de Desenvolvimento da Escola", PDE, a federal program implanted by the "Fundo de Fortalecimento da Escola" - FUNDESCOLA, which in the Ceará' s context, incorporated to the dynamic of reform of the public education. In the course of the research, I worked with the analysis of the speech and the technique of the content's analysis, penetrating in the official documents constitutelinstitute of the educational politics. In the undertaken analysis, I looked for to recover the speech while discursive materiality: bearer of contradictions, ideological load and relation of power. The speeches about the quality in the education are here conceived like historical and social events, being studied starting from them the ideological strategies of the neoliberalismo in the context of the globalization of the capital, that established a new order in the daily school on behalf of the efficiency, efficacy and the effectiveness, in detriment of the liberated and emancipated knowledge. Those ideological mechanisms are not put in an immediate form like ended data, but they are diluted in a not reflexive practice, so, I tried to study them for the methodological direction of the Analysis of the Speech complemented with the content analysis in the sense of decomposing your theoretical elements, making explicit your structure, for best to understand them. Like this, as main verification of this study detaches that the speech of the "Plano de Desenvolvimento da Escola" incorporated the official speech of the public politics of education of the decade of 1990, based on the terms: quality, efficiency, efficacy, effectiveness, modernization, administration, customer, clientele and organization. The constitution of those statements gives the conceptual terminology by a formation discursive unidirectional, revealed as knowledge pattern and educational practice, passively it accepts for the social actors in your daily ones. The official documents, representative of the educational guidelines and of the institutional decisions with relation to the quality in education denote the intentions of the public politics' formulators: to homogenize the guidelines and practices in the state public schools, in way to not to allow other speeches of revolutionary character or emancipator, hurting the possibilities of a real autonomy, participation and political praxis inside the school